Clinical significance of intrahepatic hepatitis C virus levels in patients with chronic HCV infection. Issue 4 (1st April 1998) - Haydon, G H; Jarvis, L M; Blair, C S; Simmonds, P; Harrison, D J; Simpson, K J; Hayes, P C
Abstract : Background —The clinical significance of a single assessment of circulating hepatitis C virus (HCV) RNA and its relation to the level of intrahepatic HCV RNA remains unclear. Aims —To investigate the relation between intrahepatic HCV levels and clinicopathological characteristics of chronic HCV infection. Patients —Ninety eight consecutive patients with chronic HCV infection were studied; none had received α interferon therapy. Of these, 12 patients were repeatedly negative for HCV RNA in serum by reverse transcriptase polymerase chain reaction (RT-PCR). Methods —After diagnostic laparoscopy and liver biopsy, semiquantitative analysis of intrahepatic HCV RNA levels was carried out by limiting dilution of HCV cDNA. HCV genotypes were assessed in 96 patients by restriction fragment length polymorphism analysis of HCV cDNA. Results —Ten out of 12 patients who were RT-PCR negative for HCV RNA in serum were RT-PCR positive in liver; however, this group had a significantly lower intrahepatic HCV level and serum aminotransferase level than the remaining 86 patients. Histological severity (cirrhosis: n=10); histological activity index; HCV genotype (genotype 1: n=41; genotype 2: n=12; genotype 3: n=36; genotype 4: n=7); mode of infection (intravenous drug abuse: n=58; post-transfusion: n=10; haemophiliac: n=4; sporadic: n=26) and alcohol abuse did not affect the intrahepatic virus level. There was no correlation between patient age, duration of infection, and intrahepatic HCV level. Conclusions —Intrahepatic virus levels were not determined by host factors (age of patient, mode or duration of infection) or by virus factors (HCV genotype). Repeatedly negative RT-PCR for HCV RNA in serum does not indicate absence of HCV from the liver.